De Novo Transcriptome Sequencing of Rough Lemon Leaves (Citrus jambhiri Lush.) in Response to Plenodomus tracheiphilus Infection - Riccardo Russo (International Journal of Molecular Sciences, 2021)
Mal secco is one of the most severe diseases of citrus, caused by the necrotrophic fungus Plenodomus tracheiphilus. With the main aim of identifying candidate genes involved in the response of citrus plants to “Mal secco”, we performed a de novo transcriptome analysis of rough lemon seedlings subjected to inoculation of P. tracheiphilus. The analysis of differential expressed genes (DEGs) highlighted a sharp response triggered by the pathogen as a total of 4986 significant DEGs (2865 genes up-regulated and 2121 down-regulated) have been revealed. The analysis of the most significantly enriched KEGG pathways indicated that a crucial role is played by genes involved in “Plant hormone signal transduction”, “Phenylpropanoid biosynthesis”, and “Carbon metabolism”. The main findings of this work are that under fungus challenge, the rough lemon genes involved both in the light harvesting and the photosynthetic electron flow were significantly down-regulated, thus probably inducing a shortage of energy for cellular functions. Moreover, the systemic acquired resistance (SAR) was activated through the induced salicylic acid cascade. Interestingly, RPM1 interacting protein 4, an essential positive regulator of plant defense, and BIR2, which is a negative regulator of basal level of immunity, have been identified thus representing useful targets for molecular breeding.